11. NURSES' AWARENESS OF PATIENT SAFETY AT UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL, HANOI NATIONAL UNIVERSITY IN 2023 (Vietnam Journal of Community Medicine, 2024)
Background: Patient safety is becoming an issue that receives a lot of attention from the community and also poses a big challenge to the healthcare industry. Many countries around the world have recognized that internal medicine is an important issue and are developing methods and methods to improve quality and patient safety. Internal safety is to avoid and prevent injury or adverse events during patient care [4]. The Agency for Healthcare Research and Quality defines patient safety culture as the attitudes, perceptions, competencies, and behavioral patterns of each individual healthcare worker or institution. These characteristics determine the responsibility and commitment of healthcare organizations ensuring internal safety [5]. Objective: Describe Awareness of patient safety of nurses at University of Medicine and Pharmacy Hospital, VNU in 2023. Methods: Cross-sectional survey, quantitative research. Results and conclusion: Correct awareness of positive feedback on internal safety of 150 nurses at the University of Medicine and Pharmacy Hospital is very good, specifically shown as follows: - Areas highly appreciated by medical staff include: priority management of hospital patients (>90%), good coordination between departments (94%), shift handover (88%), Dispensing drugs according to regulations at the department (90%). - Areas that need to be improved have many negative comments from health workers, including: Health workers worry about lack of support when there are errors (74.6%), health workers feel prejudiced when there are errors (41.0%), errors in prescribing drugs at the department (>50%).
Keywords: Patient safety, nursing, awareness.